PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR IPAS PADA MATERI TATA SURYA KELAS VI UPTD SDN 190 BARRU - Nur Aida Amalia.B; Syarifah Suharni (STKIP Subang, 2024)
This study aims to improve the learning outcomes of sixth-grade students at UPTD SDN 190 Barru on the Solar System material through the implementation of the Problem Based Learning (PBL) model assisted by audio-visual media. The research was conducted in two cycles using a Classroom Action Research (CAR) method. The study involved 12 students, with 6 male and 6 female participants. Pre-tests and post-tests were administered to evaluate student performance before and after the intervention. In the pre-test, the average class score was 54.2, and no student achieved the Minimum Completeness Criteria (KKM) of 75. After the PBL model with audio-visual media was applied in Cycle I, the average score increased to 75, and 50% of the students met the KKM. In Cycle II, the use of more interactive audiovisual media and structured group discussions resulted in a significant improvement, with the average score rising to 87, and 100% of the students achieved the KKM. The findings suggest that PBL, supported by audio-visual media, significantly enhances student engagement and learning outcomes. This approach is effective in addressing the challenges faced by students in understanding abstract science concepts like the Solar System